Challenges in global education in post COVID-19 era and its remedy - Rani, Ritu; Lata, Parvesh; Gorakhnath, Igona; Gupta, Bratati Das; Sanyal, Paulami (International journal of health sciences, 2022)
The whole planet has been put in danger by COVID 19. In every facet of life, it has wreaked disaster in its wake. There isn't a single industry that hasn't been touched. One of the most impacted areas is education. Around 1.54 billion children, including 743 million girls, have been infected by this outbreak, according to a UNESCO assessment. Because they lack the wherewithal to continue their education, the most disadvantaged members of society are the first to feel the effects of this policy. In these circumstances, the post-COVID-19 situation seems to be more difficult. There is a worldwide effort to assure the continuation of learning through online platforms, alternative modes of providing education, while also preparing for the opening of schools, colleges and universities. COVID 19's effects can only be mitigated if all parties involved, including students, instructors, school administration, and parents, work together to develop acceptable alternatives in concert with government authorities and educational resources. This paper will discuss about the global education system's potential problems and solutions in the years after COVID-19. Using online and virtual classrooms, it comments on the increasing reliance on technology in the classroom.